I remember nothing and other reflections - Ephron, Nora 1941-2012 (Vintage Books, 2012)
A humorous collection of personal essays discusses the author's career in journalism, divorce, a long-anticipated inheritance with unanticipated results, and the evolution of her relationship with her e-mail in-box
Hier auch später erschienene, unveränderte Nachdrucke
I remember nothing -- Who are you? -- Journalism : a love story -- The legend -- My Aruba -- My life as an heiress -- Going to the movies -- Twenty-five things people have a shocking capacity to be surprised by over and over again -- I just want to say : the egg-white omelette -- I just want to say : Teflon -- I just want to say : No, I do not want another bottle of Pellegrino -- I just want to say : the world is not flat -- I just want to say : chicken soup -- Pentimento -- My life as a meat loaf -- Addicted to L-U-V -- The six stages of e-mail -- Flops -- Christmas dinner -- The D word -- The O word -- What I won't miss -- What I will miss
Keywords: Ephron, Nora; Middle-aged women / Humor; American wit and humor; Middle aged women / Humor; Wit and humor; Altern; Erlebnisbericht